Optimalisasi penghimpunan zakat di era modern: strategi, inovasi, dan implementasi - Firmansyah, Aditya (Maliki Interdisciplinary Journal, 2025)
This article deeply examines strategies and innovations in zakat collection in the modern era, which is crucial to ensure the targeted and effective distribution of zakat funds to those who are entitled. In the context of technological advancements and changes in societal behavior, zakat institutions are required to adapt by adopting innovative and relevant collection methods. This article discusses various techniques, approaches, and breakthroughs that can be applied by zakat institutions to optimize zakat collection, including the utilization of digital platforms, social media, and the implementation of automatic payroll systems. Furthermore, this article also highlights the importance of building public trust through transparency and accountability in the management of zakat funds. The analysis includes a study of the Syafi’i school of thought’s view on zakat collection by official institutions, challenges in implementing the crowdfunding model, and the potential utilization of big data and artificial intelligence to enhance operational efficiency. This article concludes that the success of zakat collection in the modern era heavily relies on the ability of zakat institutions to innovate, build trust, and collaborate with various parties to achieve the goal of zakat as an instrument for poverty alleviation and equitable welfare distribution.